Analisis Faktor-Faktor yang Berpengaruh Terhadap Independensi Auditor - Moch. Fanni Ali Fikri; Anik Malikah; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2023)
This study aims to determine the effect of role conflict, role ambiguity, professional commitment, and ethical code compliance on auditor independence. The independent variables in this study are role conflict, role ambiguity, professional commitment, and code of ethics compliance. while the dependent variable is auditor independence. This type of research is quantitative and descriptive. The population in this study are public accountants, or KAP auditors, in Malang City. The data used in this study was premier data obtained directly from an auditor who works at the Malang City Public Accounting Firm. The data collection method used in this research is a questionnaire. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that role conflict and professional commitment have no effect on auditor independence, while role ambiguity and code of ethics compliance have a positive and significant effect on auditor independence. Simultaneously, the variables of role conflict, role ambiguity, professional commitment, and code of ethics compliance have a positive and significant effect on auditor independence.Keyword : Role conflict, role ambiguity, professional commitment, ethical code compliance on auditor independence